Developing a Digi-Preneur Business Incubator Model for MSMEs and Start-Ups in Kupang City, NTT - Noldy D.P Mumu; Supiyani Supiyani (CV Edujavare Publishing, 2025)
The development of information and communication technology has given rise to a digital economic ecosystem that opens up vast opportunities for new digital-based entrepreneurs, or digital-preneurs. This study aims to develop a relevant digital entrepreneurship–based business incubator model concept using the Research and Development (R&D) method. Through a series of stages and process, the study successfully produced a systematic and ideal design of the Digital Preneurship Business Incubator (IBDP) model as a platform for incubating MSMEs and prospective start-ups (tenants) to grow. The model, which has undergone validation and functional testing by competent experts in the field, is an advancement of the conventional business incubator model, with several crucial modifications that emphasize integrated digital aspects across all stages of the incubation process.